Photodynamic Therapy Can Induce a Protective Innate Immune Response against Murine Bacterial Arthritis via Neutrophil Accumulation - Tanaka, Masamitsu; Mroz, Pawel; Dai, Tianhong; Huang, Liyi; Morimoto, Yuji; Kinoshita, Manabu; Yoshihara, Yasuo; Nemoto, Koichi; Shinomiya, Nariyoshi; Seki, Suhji; Hamblin, Michael R. (PLOS ONE, 2012)
Background Local microbial infections induced by multiple-drug-resistant bacteria in the orthopedic field can be intractable, therefore development of new therapeutic modalities is needed. Photodynamic therapy (PDT) is a promising alternative modality to antibiotics for intractable microbial infections, and we recently reported that PDT has the potential to accumulate neutrophils into the infected site which leads to resolution of the infection. PDT for cancer has long been known to be able to stimulate the innate and adaptive arms of the immune system. Methodology/Principal Findings In the present study, a murine methicillin-resistant Staphylococcus aureus (MRSA) arthritis model using bioluminescent MRSA and polystyrene microparticles was established, and both the therapeutic (Th-PDT) and preventive (Pre-PDT) effects of PDT using methylene blue as photosensitizer were examined. Although Th-PDT could not demonstrate direct bacterial killing, neutrophils were accumulated into the infectious joint space after PDT and MRSA arthritis was reduced. With the preconditioning Pre-PDT regimen, neutrophils were quickly accumulated into the joint immediately after bacterial inoculation and bacterial growth was suppressed and the establishment of infection was inhibited. Conclusions/Significance This is the first demonstration of a protective innate immune response against a bacterial pathogen produced by PDT.